Lithium metal battery modified diaphragm, preparation method thereof and lithium metal battery

By modifying the glassy ZIF-62 layer on the lithium metal battery separator, the problem of lithium dendrites piercing the separator is solved, and the uniform transportation and deposition of lithium ions is achieved, which extends the battery cycle life and improves safety.

CN119674432APending Publication Date: 2025-03-21GUANGDONG CARBON LANGUAGE NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411930965.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Lithium metal batteries are prone to problems such as lithium dendrites piercing the diaphragm, resulting in battery capacity loss, Coulomb efficiency reduction and safety hazards.

Method used

The glassy ZIF-62 material is used as the membrane layer, and through its porous structure and grain-free characteristics, the uniform transport and deposition of lithium ions are regulated and the growth of lithium dendrites is inhibited.

Benefits of technology

The uniform transportation and deposition of lithium ions is achieved, effectively inhibiting the growth of lithium dendrites, extending the battery cycle life and improving the overall safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674432A_ABST
    Figure CN119674432A_ABST
Patent Text Reader

Abstract

The invention provides a lithium metal battery modified diaphragm, a preparation method thereof and a lithium metal battery, and relates to the technical field of lithium metal batteries. The modified lithium metal battery diaphragm comprises a lithium metal battery diaphragm and a glassy ZIF-62 layer, the glassy ZIF-62 layer modifies the lithium metal battery diaphragm, and the invention also provides a preparation method of the modified lithium metal battery diaphragm. The invention also provides a lithium metal battery which comprises the lithium metal battery modified diaphragm. The glassy ZIF-62 material disclosed by the invention has a porous structure and no grain boundary, and can regulate and control lithium ions to be uniformly transported and deposited and inhibit the growth of lithium dendrites, so that the technical problem that a lithium metal battery is easy to pierce a diaphragm by the lithium dendrites is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium metal batteries, and in particular relates to a lithium metal battery modified diaphragm and a preparation method thereof, and a lithium metal battery. Background Art

[0002] The high energy density of lithium metal batteries has attracted widespread attention. However, problems such as dendrite growth of lithium metal anode leading to diaphragm puncture still limit the commercialization of lithium metal secondary batteries. Uncontrollable lithium dendrite growth not only leads to battery capacity loss and reduced Coulomb efficiency, but also has the risk of puncturing the diaphragm, leading to internal short circuit and thermal runaway. In addition, periodic volume changes will produce unstable solid electrolyte interface (SEI) film, which will continuously consume electrolyte and further aggravate the growth of lithium dendrites. In view of the technical problem that lithium metal batteries are prone to lithium dendrite puncture of the diaphragm, the current main solutions include constructing artificial SEI film and using solid electrolyte, which can effectively inhibit the formation of dendrites and avoid short circuit due to contact between positive and negative electrodes. However, solid electrolyte materials face technical bottlenecks such as low ionic conductivity and high interface impedance. So far, there is still no practical solution to the problem of lithium dendrite growth. Therefore, it is particularly urgent to develop practical methods that can effectively inhibit the growth of lithium dendrites, extend the battery cycle life and improve the overall safety of the battery to develop lithium metal secondary batteries.

[0003] Metal organic framework (MOF) materials have attracted extensive attention due to their porous and tunable pore properties. The sub-nanometer pores provided by MOF materials can limit the transport of anions, and the ligands can also provide sites to promote lithium ion transport and inhibit non-uniform lithium deposition / stripping. Although there have been studies on the application of MOF materials in electrolytes to play a regulatory role to homogenize the transport and deposition of lithium ions, or to modify MOF materials on the surface of diaphragms to inhibit the growth of lithium dendrites, in the prior art, crystalline MOF materials are usually used as diaphragm coating materials, hoping to use the pore structure inside the crystalline MOF particles to form a uniform lithium ion flow, but the large number of grain boundaries between crystalline MOF particles will not only increase the migration energy barrier of lithium ions, but also disrupt the uniform transport of lithium ions that has been formed inside the MOF particles, resulting in the crystalline MOF material The regulatory effect on lithium ion transport behavior is counterproductive, and it is difficult to achieve uniform lithium ion transport and deposition behavior. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problem that lithium dendrites easily pierce the diaphragm in existing lithium metal batteries, and to provide a lithium metal battery modified diaphragm and its preparation method and a lithium metal battery. The glassy ZIF-62 material of the present invention has a porous structure and no grain boundaries, which can regulate the uniform transport and deposition of lithium ions and inhibit the growth of lithium dendrites.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The present invention first provides a lithium metal battery modified diaphragm, wherein the diaphragm comprises a lithium metal battery diaphragm and a glassy ZIF-62 (gZIF-62) layer;

[0007] The glassy ZIF-62 layer modifies the lithium metal battery separator.

[0008] Preferably, the lithium metal battery separator is a PP separator.

[0009] The present invention also provides a method for preparing a modified lithium metal battery diaphragm, comprising the following steps:

[0010] Step 1, mixing and stirring glassy ZIF-62, a binder and an organic solvent to obtain a glassy ZIF-62 slurry;

[0011] Step 2: coating the glassy ZIF-62 slurry obtained in step 1 on the surface of the lithium metal battery separator, and drying to obtain a lithium metal battery modified separator.

[0012] Preferably, the binder is polyvinylidene fluoride and the organic solvent is N-methylpyrrolidone.

[0013] Preferably, the mass ratio of the glassy ZIF-62 to the binder is 7:3 to 9:1; the mass ratio of the binder to the solvent is 1:49 to 1:9.

[0014] Preferably, the preparation method of the glassy ZIF-62 comprises:

[0015] Step 1, preparing crystalline ZIF-62 by hydrothermal method;

[0016] Step 2, calcining and melting the crystalline ZIF-62 prepared in step 1 in an inert gas to obtain bulk glassy ZIF-62;

[0017] Step 3: Grind the bulk glassy ZIF-62 obtained in step 2 and dry it to obtain glassy ZIF-62 powder.

[0018] Preferably, the temperature of the calcination melt quenching in step 2 is 460-520° C. and the time is 30-40 min.

[0019] Preferably, the method for preparing crystalline ZIF-62 by the hydrothermal method described in step 1 comprises the steps of:

[0020] Step 1.1, dissolving zinc nitrate hexahydrate, imidazole and benzimidazole in N,N-dimethylformamide (DMF) solution, stirring and reacting at 20-35° C. for 30-90 min to obtain a clear solution;

[0021] Step 1.2, pour the above clarified solution into a reactor for hydrothermal synthesis at 130-150° C. for 12-96 hours to obtain a crystalline ZIF-62 solution, and filter, separate, wash, and dry the solution in sequence to obtain a crystalline ZIF-62 powder.

[0022] Preferably, in step 1.1, the molar ratio of zinc nitrate hexahydrate to imidazole is 1:3.5 to 1:13.5, and the molar mass of benzimidazole accounts for 0.1 to 0.3 of the total ligand.

[0023] The present invention also provides a lithium metal battery, comprising the above-mentioned lithium metal battery modified diaphragm.

[0024] Beneficial Effects of the Invention

[0025] The present invention provides a modified lithium metal battery diaphragm, a preparation method thereof, and a lithium metal battery. The modified lithium metal battery diaphragm comprises: a lithium metal battery diaphragm and a glassy ZIF-62 (gZIF-62) layer, wherein the glassy ZIF-62 layer modifies the lithium metal battery diaphragm. Compared with crystalline MOF materials, glassy MOF materials eliminate the grain boundaries between MOF particles while maintaining the internal pore structure of crystalline MOF particles. The elimination of grain boundaries can not only reduce the energy barrier for lithium ion migration, but also prevent the migration behavior of lithium ions from being disturbed, truly realize the uniform transport and deposition of lithium ion flow, and effectively inhibit the growth of lithium dendrites, thereby solving the technical problem that lithium metal batteries are prone to lithium dendrites piercing the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The coulombic efficiency diagrams of lithium metal batteries assembled with the lithium metal battery modified separator provided in Example 1 of the present application, the lithium metal battery separator provided in Comparative Example 1, and the crystalline ZIF-62 (cZIF-62) / PP separator provided in Comparative Example 2, respectively;

[0027] Figure 2 The potential-time curves of lithium metal batteries respectively assembled with the lithium metal battery modified diaphragm provided in Example 1 of the present application, the lithium metal battery diaphragm provided in Comparative Example 1, and the cZIF-62 / PP diaphragm provided in Comparative Example 2;

[0028] Figure 3 The figure is a rate performance diagram of a Li|LiFePO4 battery using the lithium metal battery modified diaphragm provided in Example 1 of the present application and the cZIF-62 / PP diaphragm provided in Comparative Example 2;

[0029] Figure 4The potential-capacity curves of lithium metal batteries assembled with the lithium metal battery modified diaphragm provided in Example 1 of the present application, the lithium metal battery diaphragm provided in Comparative Example 1, and the cZIF-62 / PP diaphragm provided in Comparative Example 2, respectively;

[0030] Figure 5 The potential-time curves of lithium metal batteries assembled with the lithium metal battery modified diaphragm provided in Example 1 of the present application and the cZIF-62 / PP diaphragm provided in Comparative Example 2 at different rates are shown;

[0031] Figure 6 The chronoamperometric curves are respectively the chronoamperometric curves of lithium metal batteries assembled with the lithium metal battery modified diaphragm provided in Example 1 of the present application and the cZIF-62 / PP diaphragm provided in Comparative Example 2, and the insets are the electrochemical impedance spectra of the two lithium metal batteries before and after polarization;

[0032] Figure 7 They are respectively XRD spectra of the gZIF-62 material contained in the lithium metal battery modified membrane provided in Example 1 of the present application and the cZIF-62 material contained in the cZIF-62 / PP membrane provided in Comparative Example 2. DETAILED DESCRIPTION

[0033] The present invention first provides a lithium metal battery modified diaphragm, which comprises a lithium metal battery diaphragm and a glassy ZIF-62 (gZIF-62) layer; the glassy ZIF-62 layer modifies the lithium metal battery diaphragm, and the lithium metal battery diaphragm is preferably a PP diaphragm.

[0034] The present invention also provides a method for preparing a modified lithium metal battery diaphragm, comprising the following steps:

[0035] Step 1: Mix and stir the glassy ZIF-62, the binder and the organic solvent, preferably first mix and stir the binder and the organic solvent, and the stirring time is preferably 12 hours to prepare a glue; mix the glassy ZIF-62 powder and the glue and stir, and the stirring time is preferably 3 hours to obtain a glassy ZIF-62 slurry; the binder is preferably polyvinylidene fluoride (PVDF), and the organic solvent is N-methylpyrrolidone (NMP), and the mass ratio of the glassy ZIF-62 to the binder is preferably 7:3 to 9:1; the mass ratio of the binder to the solvent is preferably 1:49 to 1:9.

[0036] Step 2: coating the glassy ZIF-62 slurry obtained in step 1 on the surface of the lithium metal battery separator, and drying to obtain a lithium metal battery modified separator.

[0037] According to the present invention, the preparation method of the glassy ZIF-62 preferably comprises:

[0038] Step 1: preparing crystalline ZIF-62 by hydrothermal method; preferably comprising the following:

[0039] Step 1.1, dissolving zinc nitrate hexahydrate, imidazole and benzimidazole in N,N-dimethylformamide (DMF) solution, stirring and reacting at 20-35° C. for 30-90 minutes to obtain a clear solution; the molar ratio of zinc nitrate hexahydrate to imidazole is preferably 1:3.5-1:13.5, and the molar mass of benzimidazole accounts for 0.1-0.3 of the total ligand.

[0040] Step 1.2, pour the above clarified solution into a reactor for hydrothermal synthesis at 130-150°C for 12-96h to obtain a crystalline ZIF-62 solution, and filter the solution, wash and dry it in turn to obtain a crystalline ZIF-62 powder. The solvent for the filtration and washing is preferably DMF and dichloromethane; the drying temperature is preferably 100-150°C, and the drying time is preferably 8-12h.

[0041] Step 2, calcining and melting quenching the crystalline ZIF-62 prepared in step 1 in an inert gas, wherein the temperature of the calcining and melting quenching is preferably 460 to 520° C., and the time is preferably 30 to 40 minutes, to obtain bulk glassy ZIF-62;

[0042] Step 3: Grind the bulk glassy ZIF-62 obtained in step 2 and dry it to obtain glassy ZIF-62 powder.

[0043] According to the present invention, the glassy ZIF-62 slurry is coated on the surface of the lithium metal battery separator and dried to obtain the lithium metal battery modified separator, comprising the steps of:

[0044] Step 2.1, coating the glassy ZIF-62 slurry on the surface of the pretreated lithium metal battery separator with a scraper having a height of 100 μm to obtain a lithium metal battery modified wet separator;

[0045] Step 2.2, coating the diaphragm surface is single-sided coating or double-sided coating;

[0046] Step 2.2: vacuum dry the lithium metal battery modified wet diaphragm at 55-65° C. for 3-12 hours to obtain a lithium metal battery modified diaphragm.

[0047] The present invention also provides a lithium metal battery, comprising the above-mentioned lithium metal battery modified diaphragm.

[0048] The present invention is further described in detail below with reference to specific examples, and the raw materials involved in the examples are all commercially available.

[0049] Example 1

[0050] This embodiment 1 provides a method for preparing a modified lithium metal battery diaphragm, the preparation method comprising the following steps:

[0051] Step 1: Preparation of crystalline ZIF-62, i.e. cZIF-62:

[0052] Step 1.1, 6.8574 g of zinc nitrate hexahydrate and 20.259 g of imidazole were dissolved in 170 mL of DMF solution and stirred for 30 min, and then 2.8351 g of benzimidazole was added to dissolve to obtain a clear solution.

[0053] Step 1.2, add the obtained solution into a reactor and carry out hydrothermal reaction at 130°C for 48 hours to obtain crystalline ZIF-62, filter and wash it, and vacuum dry it at 150°C.

[0054] Step 2: Melt quenching to obtain glassy ZIF-62, i.e. gZIF-62:

[0055] Step 2.1. Weigh a certain amount of cZIF-62 and put it into a porcelain boat. Calcine it at 460°C in a tubular furnace using an argon atmosphere until it is molten, and then quench and cool to obtain block gZIF-62, which is then ground into powder for later use.

[0056] Step 3: Preparation of modified lithium metal battery diaphragm:

[0057] Step 3.1, 0.82 g PVDF and 15 mL NMP were mixed and stirred for 12 h to prepare PVDF glue with a mass fraction of 5%;

[0058] Step 3.2, mix 30 mg of the gZIF-62 powder obtained in step 2 with 1.5 g of PVDF glue and stir for 3 h;

[0059] Step 3.3: Use a scraper with a height of 100 μm to evenly coat the gZIF-62 slurry on the surface of the PP diaphragm, and then vacuum dry it at 60°C for 12 h. Repeat step 3.2 for double-sided coating, and finally punch out a diaphragm with a diameter of 19 mm.

[0060] Comparative Example 1

[0061] This comparative example 1 provides a method for preparing a lithium metal battery separator, and the preparation method comprises the following steps: using a commercially available PP separator Celgard2400, and punching a separator with a diameter of 19 mm using a cutting machine.

[0062] Comparative Example 2

[0063] This comparative example 2 provides a method for preparing a crystalline ZIF62 (cZIF-62) modified diaphragm (cZIF-62 / PP), the preparation method comprising the following steps:

[0064] Step 1: Preparation of cZIF-62 powder:

[0065] Step 1.1, 6.8574 g of zinc nitrate hexahydrate and 20.259 g of imidazole were dissolved in 170 mL of DMF solution and stirred for 30 min, and then 2.8351 g of benzimidazole was added and dissolved to obtain a clear solution.

[0066] Step 1.2: Add the obtained clear solution into a reactor, and carry out hydrothermal reaction at 130°C for 48 hours to obtain crystalline cZIF-62, which is then filtered and washed, and then vacuum dried at 150°C.

[0067] Step 2: Preparation of cZIF-62 / PP membrane:

[0068] Step 2.1, 0.82 g PVDF and 15 mL NMP were mixed and stirred for 12 h to prepare PVDF glue with a mass fraction of 5%, and 30 mg of cZIF-62 obtained in step 1 was mixed and stirred with 1.5 g PVDF glue for 3 h to obtain cZIF-62 slurry;

[0069] Step 2.2: Use a scraper with a height of 100 μm to evenly coat the cZIF-62 slurry on the surface of the PP diaphragm, and vacuum dry it at 60° C. Repeat step 2.2 for double-sided coating, and finally punch out a diaphragm with a diameter of 19 mm.

[0070] Example 2

[0071] This Example 2 is to test the electrochemical performance of lithium metal batteries assembled using the lithium metal battery modified diaphragm provided in Example 1 of the present application, the lithium metal battery diaphragm provided in Comparative Example 1, and the cZIF-62 / PP diaphragm provided in Comparative Example 2.

[0072] The assembly process of a lithium metal battery including a lithium metal battery modified diaphragm provided in Example 1 of the present application includes first assembling the diaphragm into a Li|Cu battery, a Li|LiFePO4 battery and a Li|Li symmetric battery in a glove box filled with high-purity argon gas, the negative electrode uses a lithium sheet, the electrolyte is 1M LiTFSI-DOL / DME (V:V=1:1) + 1wt% anhydrous lithium nitrate, and assembling into a CR2032 type button battery, and the assembled button battery is left to stand at room temperature 25°C for 8 hours.

[0073] The assembly process of the lithium metal battery including the lithium metal battery separator and cZIF-62 / PP separator provided in Comparative Examples 1 and 2 of the present application is the same as that in Example 1.

[0074] The performance tests of lithium metal batteries based on the lithium metal battery modified diaphragm provided in Example 1 of the present application, the lithium metal battery diaphragm provided in Comparative Example 1, and the cZIF-62 / PP diaphragm provided in Comparative Example 2 respectively include lithium metal battery coulomb efficiency test, potential-time curve test, and rate performance test. The current density of the coulomb efficiency and potential-time curve tests is set to 0.5 mA cm -2 , with a capacity of 0.5 mAh cm -2 ;

[0075] The coulombic efficiency test results of three Li|Cu batteries are shown in the attached Figure 1 As shown, the results show that compared with Comparative Examples 1 and 2, the Coulombic efficiency of the Li|Cu battery including the lithium metal battery modified diaphragm provided in Example 1 of the present application after 120 cycles is 95.95%, while the Coulombic efficiency of the Li|Cu battery based on the lithium metal battery diaphragm provided in Comparative Example 1 drops sharply after 15 cycles and fluctuates greatly; the Coulombic efficiency of the Li|Cu battery assembled based on the cZIF-6 / PP diaphragm provided in Comparative Example 2 after 120 cycles is only 50.69%.

[0076] The potential-time curves of three Li|Li symmetric batteries are shown in the attached figure. Figure 2 As shown, the results show that the potential polarization value of the Li|Li symmetric battery including the modified diaphragm of the lithium metal battery provided in Example 1 of the present application is about 20.5mV after 700h of cycling, and it has been very stable; the potential polarization value of the Li|Li symmetric battery based on the lithium metal battery diaphragm provided in Comparative Example 1 is about 60mV after 200h of cycling, and the polarization gradually increases. After 400h of cycling, the potential drops sharply, indicating that the battery has a micro-short circuit; the Li|Li symmetric battery based on the cZIF-62 / PP diaphragm provided in Comparative Example 2 suddenly increases from 25mV to 60mV after 210h of cycling, and then continues to increase gradually. The above experimental results show that compared with the comparative example, the Li|Li symmetric battery based on the modified diaphragm of the lithium metal battery provided in Example 1 of the present application exhibits smaller potential polarization and longer cycle life.

[0077] The rate performance test results of Li|LiFePO4 battery are shown in the attached Figure 3 As shown, the results show that the rate performance of the battery based on the lithium metal battery modified diaphragm provided in Example 1 of the present application is better than that of the battery based on the cZIF-62 / PP diaphragm provided in Comparative Example 2.

[0078] The potential-capacity curves of Li|Cu batteries based on three types of separators are shown in the attached figure. Figure 4As shown, the results show that in the Li|Cu battery based on the modified lithium metal battery diaphragm provided in Example 1 of the present application, the nucleation overpotential of lithium metal is about 34.5mV, while in the Li|Cu battery based on the lithium metal battery diaphragm provided in Comparative Example 1 of the present application, the nucleation overpotential of lithium metal is 41.6mV; in the Li|Cu battery based on the cZIF-62 / PP diaphragm provided in Comparative Example 2 of the present application, the nucleation overpotential of lithium metal is about 36.3mV. The above experimental results show that compared with the comparative battery, the battery based on the modified lithium metal battery diaphragm provided in Example 1 of the present application exhibits a smaller lithium metal nucleation overpotential.

[0079] The potential-time curves of three Li|Li symmetric batteries at different rates are shown in the attached figure. Figure 5 The results show that the Li|Li symmetric battery based on the lithium metal battery modified diaphragm provided in Example 1 of the present application has a current density of 0.5 mA cm -2 、1mAcm -2 , 2mA cm -2 , 4mA cm -2 , 0.5mA cm -2 The potential polarization values ​​stabilized at about 26 mV, 41.8 mV, 51.5 mV, and 80 mV, respectively, and finally returned to a current density of 0.5 mA cm -2 When the potential polarization value is about 20.9 mV, it is significantly smaller than the potential polarization value of the Li|Li symmetric battery based on the cZIF-62 / PP separator provided in Comparative Example 2 at the corresponding current density, and the battery in Comparative Example 2 returns to the current density of 0.5 mA cm -2 The above experimental results show that compared with the battery of Comparative Example 2, the battery based on the lithium metal battery modified separator provided in Example 1 has better rate performance.

[0080] The test results of lithium ion migration number in lithium metal batteries based on different separators are shown in the attached figure. Figure 6 As shown, the results show that the lithium ion migration number of the lithium metal battery based on the lithium metal battery modified diaphragm provided in Example 1 of the present application is about 0.9, and the lithium ion migration number of the lithium metal battery based on the cZIF-62 / PP diaphragm provided in Comparative Example 2 is about 0.88. The above experimental results show that compared with the battery in Comparative Example 2, the battery based on the lithium metal battery modified diaphragm provided in Application Example 1 is more conducive to the transmission of lithium ions.

[0081] Figure 7The XRD spectra of the gZIF-62 material contained in the lithium metal battery modified diaphragm provided in Example 1 of the present application and the cZIF-62 material contained in the cZIF-62 / PP diaphragm provided in Comparative Example 2 are shown. The results show that the cZIF-62 material exhibits obvious diffraction peaks, proving that it is crystalline; while the XRD spectrum of the gZIF-62 material shows a "mantou peak", proving that it is amorphous.

Claims

1. A modified lithium metal battery diaphragm, characterized in that: The separator includes a lithium metal battery separator and a glassy ZIF-62 layer; The glassy ZIF-62 layer modifies the lithium metal battery separator.

2. A lithium metal battery modified diaphragm according to claim 1, characterized in that: The lithium metal battery separator is a PP separator.

3. The method for preparing a modified lithium metal battery diaphragm according to claim 1, characterized in that: The following steps are involved: Step 1, mixing and stirring glassy ZIF-62, a binder and an organic solvent to obtain a glassy ZIF-62 slurry; Step 2: coating the glassy ZIF-62 slurry obtained in step 1 on the surface of the lithium metal battery separator, and drying to obtain a lithium metal battery modified separator.

4. The method for preparing a modified lithium metal battery diaphragm according to claim 3, characterized in that: The binder is polyvinylidene fluoride, and the organic solvent is N-methyl pyrrolidone.

5. The method for preparing a modified lithium metal battery diaphragm according to claim 3, characterized in that: The mass ratio of the glassy ZIF-62 to the binder is 7:3 to 9:1; the mass ratio of the binder to the solvent is 1:49 to 1:

9.

6. The method for preparing a modified lithium metal battery diaphragm according to claim 5, characterized in that: The preparation method of the glassy ZIF-62 comprises: Step 1, preparing crystalline ZIF-62 by hydrothermal method; Step 2, calcining and melting the crystalline ZIF-62 prepared in step 1 in an inert gas to obtain bulk glassy ZIF-62; Step 3: Grind the bulk glassy ZIF-62 obtained in step 2 and dry it to obtain glassy ZIF-62 powder.

7. The method for preparing a modified lithium metal battery diaphragm according to claim 6, characterized in that: The temperature of the calcination, melting and quenching in step 2 is 460-520° C. and the time is 30-40 minutes.

8. The method for preparing a modified lithium metal battery diaphragm according to claim 6, characterized in that: The method for preparing crystalline ZIF-62 by the hydrothermal method described in step 1 comprises the steps of: Step 1.1, dissolving zinc nitrate hexahydrate, imidazole and benzimidazole in N,N-dimethylformamide (DMF) solution, stirring and reacting at 20-35° C. for 30-90 min to obtain a clear solution; Step 1.2, pour the above clarified solution into a reactor for hydrothermal synthesis at 130-150° C. for 12-96 hours to obtain a crystalline ZIF-62 solution, and filter, separate, wash, and dry the solution in sequence to obtain a crystalline ZIF-62 powder.

9. The method for preparing a modified lithium metal battery diaphragm according to claim 8, characterized in that: In step 1.1, the molar ratio of zinc nitrate hexahydrate to imidazole is 1:3.5 to 1:13.5, and the molar mass of benzimidazole accounts for 0.1 to 0.3 of the total ligand.

10. A lithium metal battery, characterized in that: The invention comprises the modified lithium metal battery diaphragm as claimed in claim 1.

Citation Information

Cited By

  • Polypyrrole modified diaphragm, preparation method and metal lithium battery

    CN122494992A